Efectos de la terapia geotermal en el tratamiento del dolor muscular cervical y lumbar en pacientes que acuden al área de rehabilitación del Hospital Básico Dr. Publio escobar del cantón Colta junio – noviembre 2016 - Arévalo Barriga, Fabyana Gabriela (2017)
Throughout history, cultures around the world have used hot stones for therapeutic or curative purposes, Japanese monks appealed to the use of heated disc-shaped stones to relieve pain, American Indian women placed hot stones on the belly to relieve menstrual cramps; the present research was carried out in the Province of Chimborazo, Colta Canton, Cajabamba Parish at the Basic Hospital “Dr. Publio Escobar Gómez”, which is directed to determine the effects of geothermal therapy in the treatment of cervical an lumbar muscle pain. Geothermal Therapy is inspired by the Eastern disciplines, it is an integrative technique that combines the global effects of Thermotherapy, the neuro-sedative effects of Masotherapy and the millenary knowledge of Geotherapy, producing physiological and organic reactions of the highest benefit for being human. The research was descriptive and qualitative because the pathology was explained in detail; because its nature was documentary and field since the information was acquired in books, charts of evolution, physiotherapeutic records; the type of study was longitudinal due to data were obtained from a group of patients with similar characteristics. In the verification of the results of the initial and final Numerical pain scale, it was found that of the 55 patients at the end of the treatment, 73% were found to be pain free, 18% with mild pain and 9% with moderate pain: proving the effectiveness